Scavenging sunblock agents from aquatic environment through encapsulation in cucurbit[7]uril - Faizan Ullah; Maria Maqbool; Nadeem S. Sheikh; Imene Bayach; Khurshid Ayub (Scientific Reports)
Abstract Here, the encapsulation behavior of Cucurbit[7]uril (CB[7]) is studied for six organic UV filters, i.e., benzophenone, homosalate, oxybenzone, dioxybenzone, sulisobenzone, and para aminobenzoic acid (PABA) using density functional theory (DFT). The thermodynamic stability of the designed systems is ensured by the values of interaction energies ranging from − 11.78 to -20.42 kcal/mol, with the highest value observed for dioxybenzone@CB[7]. Non-covalent interaction (NCI) analysis highlights the prevalence of van der Waals interactions in host-guest complexes, supported by quantum theory of atoms in molecule (QTAIM) analysis. The values of interaction energies of individual bonds in QTAIM analysis fall below 3 kcal/mol confirming the van der Waals interactions between the host and guest species. Frontier molecular orbital (FMO) and density of states (DOS) analyses indicate decreased energy gaps in the complexes compared to bare species, while natural bond orbital (NBO) analysis reveals charge transfer from host to guests with the highest observed for oxybenzone@CB[7] (-0.019|e|). Recovery time and desorption energy analysis highlight dioxybenzone@CB[7] as the most strongly adsorbed complex, while benzophenone@CB[7] being the least. The analysis also suggest a decrease in recovery time with increasing temperature (i.e., least for benzophenone@belt complex, i.e., 2.7 $$\:×\:$$ 10−6 s at 400 K). These findings illustrate CB[7] as an efficient host for encapsulating organic UV filters, offering a promising approach for reducing their negative ecological consequences.